Answer:
(2,2) and (3,1)
Step-by-step explanation:
Since we're given the value of y in the second equation, we can replace the y on the left side of the first equation with 4-x, giving us
![4-x=x^2-6x+10\\0=x^2-5x+6](https://tex.z-dn.net/?f=4-x%3Dx%5E2-6x%2B10%5C%5C0%3Dx%5E2-5x%2B6)
We can factor the expression on the right to get us
![0=x^2-5x+6\\0=x^2-3x-2x+6\\0=x(x-3)-2(x-3)\\0=(x-2)(x-3)](https://tex.z-dn.net/?f=0%3Dx%5E2-5x%2B6%5C%5C0%3Dx%5E2-3x-2x%2B6%5C%5C0%3Dx%28x-3%29-2%28x-3%29%5C%5C0%3D%28x-2%29%28x-3%29)
Solving
and
gets us the solutions
, which we can plug into the second equation to get us
![y=4-2=2\\y=4-3=1](https://tex.z-dn.net/?f=y%3D4-2%3D2%5C%5Cy%3D4-3%3D1)
So, our solution set is the pair of points (2,2) and (3,1)